2014
DOI: 10.1542/peds.2013-3348
|View full text |Cite
|
Sign up to set email alerts
|

Postmarketing Trials and Pediatric Device Approvals

Abstract: BACKGROUND: Medical devices can be useful in a variety of diseases, but few devices have been specifically approved for use in children. The 2007 Pediatric Medical Device Safety and Improvement Act was passed to stimulate pediatric device development. The current state of trial evidence underpinning the approval of pediatric devices remains poorly described. METHODS: We identified all high-risk (ie, class III) devices approve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 19 publications
4
37
0
Order By: Relevance
“…7 As one part of this approach, the FDA can require additional clinical studies as a condition of PMA approval through its postapproval studies (PAS) program. 8 However, PAS may often be small, 9 delayed, 9,10 or not generalizable 5,11 ; in addition, only one-quarter of PAS required by the FDA between 2005 and 2011 were completed. 9 Beyond FDA-required postmarket studies, complementary sources of evidence may be generated through studies initiated by manufacturers or independent investigators, although manufacturers may conduct postmarket clinical studies primarily to comply with regulatory requirements.…”
Section: -5mentioning
confidence: 99%
“…7 As one part of this approach, the FDA can require additional clinical studies as a condition of PMA approval through its postapproval studies (PAS) program. 8 However, PAS may often be small, 9 delayed, 9,10 or not generalizable 5,11 ; in addition, only one-quarter of PAS required by the FDA between 2005 and 2011 were completed. 9 Beyond FDA-required postmarket studies, complementary sources of evidence may be generated through studies initiated by manufacturers or independent investigators, although manufacturers may conduct postmarket clinical studies primarily to comply with regulatory requirements.…”
Section: -5mentioning
confidence: 99%
“…In certain premarket studies, safety and effectiveness of medical devices used in adolescents have been extrapolated from adult data. Hwang et al 3 found that most of the recently approved pediatric devices have been approved on the basis of adult studies. There are unique issues that should be considered in device use for adolescents.…”
Section: Medical Device Study Considerations For Adolescentsmentioning
confidence: 99%
“…In other words, the projected profitability from pediatric device development is outstripped by the resources required to bring a device to market. As such, most devices used in pediatrics have not been rigorously studied in pediatric patients (10) and many unmet needs exist in this population. Programs and initiatives designed to help innovators address urgent unmet clinical needs such as those for pediatric patients are discussed below.…”
Section: The Unmet Clinical Needmentioning
confidence: 99%